Please copy and paste this embed script to where you want to embed

A-Math Formula List - Additional Math (4047) *Formulas highlighted in yellow are found in the formula list of the exam paper.

Quadratic Equation b2 - 4ac > 0 Real and Distinct Roots Also known as Unequal Roots

b2 - 4ac = 0 Real and Equal Roots Also known as Repeat Roots or Coincident Roots.

b2 - 4ac < 0 Imaginary roots Also known as Complex Roots.

b2 - 4ac > 0 Real and Distinct Roots Also known as Unequal Roots

b2-4ac = 0 Real and Equal Roots Also known as Repeat Roots or Coincident Roots.

b2-4ac < 0 Imaginary roots Also known as Complex Roots

Page 1 of 12 www.tuitionwithjason.sg

A-Math Formula List - Additional Math (4047) Roots of Quadratic Equation The Quadratic Equation has solutions 𝛼 and 𝛽 Sum of Roots is 𝛼 + 𝛽 = −

𝑏

Product of Roots is 𝛼𝛽 =

𝑎

The Equation is x2 – (Sum of Roots) x + (Product of Roots) = 0

𝛼 2 + 𝛽 2 = (𝛼 + 𝛽)2 − 2𝛼𝛽

𝑐

𝑎

𝛼 − 𝛽 = ±�(𝛼 − 𝛽)2

𝛼 4 + 𝛽 4 = (𝛼 2 + 𝛽 2 )2 − 2(𝛼𝛽)2

Indices Same Base Number

Same Power

x a × xb = x a +b

a × b =( a × b )

xa = x a −b xb

a a = m b b

(x )

a b

m

m

m

Same Base Number→ Power Add or Subtract

m

Same Power same→ Base Number Multiply or Divide.

m

= x a×b ≠ x a × xb = x a +b

Other Laws of Indices 1 b

1 xa

x−a =

x a y −b =

x = b x1

xa yb

1 = xa x−a a b

x = x b

a

−

1

b x=

x y −

a b

x=

1 = 1 b x −a

x0 = 1

1 b

x1

y = x

1 = a xb

a

1 b

xa

Page 2 of 12 www.tuitionwithjason.sg

A-Math Formula List - Additional Math (4047) Surds a a÷ b= b

a × b = a×b

( a )=

m a ×n b = m× n a×b

2

a × a=

a

m a +n a = ( m + n) a

m a −n a = ( m − n) a

Rationalizing Denominator 1 n− a × = n+ a n− a

(n − n −(

1 n+ a × = n− a n+ a

(n + n −(

1 n+

1 n−

a

a

2

2

) a)

(n −

) a)

(n −

a

a

= 2

= 2

a

)

n −a 2

a

)

n −a 2

×

n− a = n− a

( n − a= ) (n − a ) n−a ( n) −( a)

×

n+ a = n+ a

( n + a= ) (n + a ) n−a ( n) −( a)

2

2

2

2

Partial Factions Linear Factor Check if the highest coefficient of the

mx + n A B = + (ax + b)(cx − d ) (ax + b) (cx + d )

NUMERATOR is the SAME or LARGER that the DENOMINATOR. If it is, do LONG DIVISION first before partial

Repeat Factor

fractions.

mx + n A B C = + + 2 (ax + b)(cx − d ) (ax + b) (cx + d ) (cx + d ) 2

Page 3 of 12 www.tuitionwithjason.sg

A-Math Formula List - Additional Math (4047) Quadratic Factor mx + n A Bx + C = + 2 (ax + b)(cx − d ) (ax + b) (cx 2 + d )

Logarithm log b 1 = 0

ln1 = 0

log b b = 1

ln e x = x

by = x can be covert to y = log b x

log b bx = x log b m + log b n = log b (m × n) log b m – log b n = log b (m ÷ n)

ln e xa = xa * log b (m × n) ≠ log b m × log b n

ln x = log e x ln e =1 as log e e=1

log b m a = a × log b m log v u =

log a u log a v

log = vu

log u u 1 = log u v log u v

Binomial Expansion n n! = r r !(n − r )!

n n = Cr r

n n n n n n bx)n a n (bx)0 + a n −1 (bx)1 + a n −2 (bx)2 + a n −3 (bx)3 .... a n −r (bx)r + a n −n (bx)n (a += 0 1 2 3 r n OR

n n n n a n + a n −1 (bx)1 + a n − 2 (bx) 2 + a n −3 (bx)3 .... a n − r (bx) r + (bx) n (a + bx) n = 1 2 3 r

Page 4 of 12 www.tuitionwithjason.sg

A-Math Formula List - Additional Math (4047) n (n)(n − 1) n − 2 (n)(n − 1)(n − 2) n −3 a n + a n −1 (bx)1 + a (bx) 2 + a (bx)3 .... + (bx) n (a + bx) n = 1 1× 2 1× 2 × 3

n n n n −1 n n−2 n n −( n −1) n 0 1 2 n −1 n ( kx ) + 1n−n ( kx ) 1 ( kx ) + 1 ( kx ) + 1 ( kx ) + .... 1 0 1 2 n − 1 n

kx ) (1 += n

OR

(1 + kx )

n

n n n n −1 n 1 2 = 1 + ( kx ) + ( kx ) + .... ( kx ) + ( kx ) 1 2 n − 1

Trigonometry

cos ecθ =

1 sin θ

sin 2 θ + cos 2 θ = 1

sec θ =

1 cos θ

1 + cot 2 θ = cos ec 2θ

cot θ =

1 cos θ = tan θ sin θ

1 + tan 2 θ = sec 2 θ

Compound Angle Formula

sin ( A= ± B ) sin A cos B ± cos A sin B

cos ( A ± B ) = cos A cos B sin A sin B

Page 5 of 12 www.tuitionwithjason.sg

A-Math Formula List - Additional Math (4047) tan A ± tan B tan ( A ± B ) = 1 tan A tan B

Double Angle Formula

sin 2 A = 2sin A cos A

cos = 2 A cos 2 A − sin 2 A

tan 2 A =

= cos 2 A 2 cos 2 A − 1

2 tan A 1 − tan 2 A

cos 2 A = 1 − 2sin 2 A

Half Angle Formula

sin

A 1 − cos A = ± 2 2

cos

A 1 + cos A = ± 2 2

A = tan 2

1 − cos A 1 − cos A = 1 + cos A sin A

R-Formula aCosθ ± bSinθ = RCos (θ α )

R Where=

aSinθ ± bCosθ = RSin(θ ± α )

tan α =

a 2 + b2

b a

Co-ordinate Geometry Gradient(m) =

y2 − y1 x2 − x1

Linear Graph Y= m x + c

y2 − y= m( x2 − x1 ) 1 m= gradient

General Equation

c= y-intercept (point on the graph that intersects the y-axis)

Y − y1= m( X − x1 ) where

( x1 , y1 ) is a point on the

graph.

Page 6 of 12 www.tuitionwithjason.sg

A-Math Formula List - Additional Math (4047) Mid-point of a line = (

x1 + x2 y1 + y2 , ) 2 2

Distance between two points =

( x2 − x1 ) 2 + ( y2 − y1 ) 2

If two lines have the same gradient

If two line have perpendicular

m1 = m2

gradient i.e. 90° to each other.

m1 = −

1 or m1 × m2 = −1 m2

Perpendicular Bisector

1. The two lines AB and PQ must intersect at 90°

m1 ( AB ) = −

1 m2 ( PQ)

2. One Line (AB) will cut the mid-point of the other line (PQ)

x2 + x1 y2 + y1 , 2 2

Mid-point PQ =

Area of Plane Figure (Polygon Figure)

Vertices A(x1,y1), B(x2,y2),C (x3,y3)

1 𝑥1 � 2 𝑦1

*It does NOT matter if you calculate in a

𝑥2 𝑥3 𝑦2 𝑦3

𝑥4 𝑦4

𝑥1 𝑦1 �

clockwise or anti-clockwise direction. The is a |modulus| in the formula

1 |(𝑥 𝑦 + 𝑥2 𝑦3 + 𝑥3 𝑦4 + 𝑥4 𝑦1 ) − (𝑥2 𝑦1 + 𝑥3 𝑦2 + 𝑥4 𝑦3 + 𝑥1 𝑦4 )| 2 1 2

Page 7 of 12 www.tuitionwithjason.sg

A-Math Formula List - Additional Math (4047) Circles Radius of a circle r=

( x − a ) 2 + ( y − b) 2

Equation of a Circle (𝑥 − 𝑎)2 + (𝑦 − 𝑏)2 = 𝑟 2 or

𝑥 2 + 𝑦 2 + 2𝑔𝑥 + 2𝑓𝑦 + 𝑐 = 0

where 𝑎 = −𝑔, 𝑏 = −𝑓 and 𝑟 = �𝑔2 + 𝑓 2 − 𝑐

Proofs in Plane Geometry Midpoint Theorem

Tangent –Chord Theorem (Alternate Segment Theorem)

sin If X and Y are midpoints, then

Angle W = Angle X

YZ // WX

Angle Y = Angle Z

YZ = ½ WX

Differentiation dy (ax n ) = anx n −1 dx

dy (ax) = a dx

dy (a) = 0 dx

Where’ a’ is a constant and ‘n’ is an integer.

Page 8 of 12 www.tuitionwithjason.sg

A-Math Formula List - Additional Math (4047) Chain Rule

Sum/Difference of Function

dy dy du = × dx du dx

d du dv (u ± v) = ± dx dx dx

Product Rule

Quotient Rule

d dv du (= uv) u + v dx dx dx

du dv v −u d u dx dx = dx v v2

d (sin x) = cos x dx

d (cos x) = − sin x dx

d (tan x) = sec 2 x dx

The functions below are obtained using chain rule.

d c ) ab cos(bx + c) a sin ( bx += dx

d −ab sin(bx + c) a cos ( bx + c ) = dx

d + c ) ab sec 2 (bx + c) a tan ( bx = dx

d a sin n ( bx = + c ) anb sin n −1 (bx + c) cos(bx + c) dx

d a cos n ( bx + c ) = − anb cos n −1 (bx + c) sin(bx + c) dx d ata n n ( bx = + c ) anb tan n −1 (bx + c) sec 2 (bx + c) dx

Exponential/Natural Logarithm Function d x (e ) = e x dx

d ax +b (e ) = ae ax +b (where a and b are constants) dx

d 1 (ln x) = (where x>0) dx x

d a [ln(ax + b)] = (where ax +b>0) dx ax + b

Page 9 of 12 www.tuitionwithjason.sg

A-Math Formula List - Additional Math (4047) Integration n dx ∫ ax=

ax n +1 + c where n≠1 n +1

∫ a dx= ax + c

∫ ( ax + b )

n

( ax + b )

= dx

n +1

(n + 1)(a )

+c

n≠1,a≠0; a & b are constants Product of constant and a function

Sum and Difference of function

∫ af ( x)dx = a ∫ f ( x)dx

∫ [α f ( x) ± β g ( x)]dx = α ∫ f ( x)dx ± β ∫ g ( x)dx

bx dx ∫ a cos=

where f(x) is a function

a sin bx + c b

a

− cos bx + c ∫ a sin bx dx = b

bx dx ∫ a sec= 2

a tan bx + c b

where x is in radian.

1 dx ln x + c where x>0 ∫x=

∫e

x

dx= e x + c

�

1 ln(𝑎𝑥 + 𝑏) 𝑑𝑥 = +𝐶 𝑎𝑥 + 𝑏 𝑎

�𝑒

𝑎𝑥+𝑏

𝑒 𝑎𝑥+𝑏 𝑑𝑥 = +𝐶 𝑎

�

1 ln(𝑎𝑥 2 + 𝑏𝑥) 𝑑𝑥 = +𝐶 𝑎𝑥 2 + 𝑏𝑥 2𝑎𝑥 + 𝑏

�𝑒

𝑎𝑥 2 +𝑏𝑥

2

𝑒 𝑎𝑥 +𝑏𝑥 𝑑𝑥 = +𝐶 2𝑎𝑥 + 𝑏

Page 10 of 12 www.tuitionwithjason.sg

A-Math Formula List - Additional Math (4047)

Integration of Area Area between Curve and X-axis 𝑏

∫𝑎 𝑓(𝑥)𝑑𝑥 Area between Curve and X-axis 𝑏

− ∫𝑎 𝑓(𝑥)𝑑𝑥 Area between Curve and Y-axis 𝑏

∫𝑎 𝑓(𝑦)𝑑𝑦 Area between Curve and Y-axis 𝑏

− ∫𝑎 𝑓(𝑦)𝑑𝑦

Area between the Curves f(x) (u-shape) and g(x)(n-shape). 𝑏

𝑏

� 𝑔(𝑥)𝑑𝑥 − � 𝑓(𝑥)𝑑𝑥 𝑎

𝑎

Area between the Curves g(x)(n-shape) and f(x)(u-shape). 𝑏

𝑏

−[� 𝑓(𝑥)𝑑𝑥 − � 𝑔(𝑥)𝑑𝑥] 𝑎

𝑎

Page 11 of 12 www.tuitionwithjason.sg

A-Math Formula List - Additional Math (4047) Area between the Curves g(y) (inverted c-shape) and f(y) (c-shape). 𝑏

𝑏

� 𝑔(𝑦)𝑑𝑦 − � 𝑓(𝑦)𝑑𝑦 𝑎

𝑎

Area between the Curves f(y) (c-shape) and g(y) (inverted c-shape). 𝑏

𝑏

−[∫𝑎 𝑓(𝑥)𝑑𝑥 − ∫𝑎 𝑔(𝑥)𝑑𝑥]

Kinematics Velocity is the RATE of CHANGE of

Acceleration is the RATE of CHANGE of

Displacement

Velocity

v=

ds dt

a=

where v: velocity,s:displacement, t:time = v

where a:accleration Some other methods to find acceleration

dv

a dt ∫ dt ∫= dt

= a

Displacement (s)

dv dt

𝑑𝑠 𝑑𝑡

Velocity (v)

� 𝑣 𝑑𝑡

d 2s dt 2

= a

𝑑𝑣 𝑑𝑡

dv ds × ds dt

Acceleration (a)

� 𝑎 𝑑𝑡 The End

Page 12 of 12 www.tuitionwithjason.sg

View more...
Quadratic Equation b2 - 4ac > 0 Real and Distinct Roots Also known as Unequal Roots

b2 - 4ac = 0 Real and Equal Roots Also known as Repeat Roots or Coincident Roots.

b2 - 4ac < 0 Imaginary roots Also known as Complex Roots.

b2 - 4ac > 0 Real and Distinct Roots Also known as Unequal Roots

b2-4ac = 0 Real and Equal Roots Also known as Repeat Roots or Coincident Roots.

b2-4ac < 0 Imaginary roots Also known as Complex Roots

Page 1 of 12 www.tuitionwithjason.sg

A-Math Formula List - Additional Math (4047) Roots of Quadratic Equation The Quadratic Equation has solutions 𝛼 and 𝛽 Sum of Roots is 𝛼 + 𝛽 = −

𝑏

Product of Roots is 𝛼𝛽 =

𝑎

The Equation is x2 – (Sum of Roots) x + (Product of Roots) = 0

𝛼 2 + 𝛽 2 = (𝛼 + 𝛽)2 − 2𝛼𝛽

𝑐

𝑎

𝛼 − 𝛽 = ±�(𝛼 − 𝛽)2

𝛼 4 + 𝛽 4 = (𝛼 2 + 𝛽 2 )2 − 2(𝛼𝛽)2

Indices Same Base Number

Same Power

x a × xb = x a +b

a × b =( a × b )

xa = x a −b xb

a a = m b b

(x )

a b

m

m

m

Same Base Number→ Power Add or Subtract

m

Same Power same→ Base Number Multiply or Divide.

m

= x a×b ≠ x a × xb = x a +b

Other Laws of Indices 1 b

1 xa

x−a =

x a y −b =

x = b x1

xa yb

1 = xa x−a a b

x = x b

a

−

1

b x=

x y −

a b

x=

1 = 1 b x −a

x0 = 1

1 b

x1

y = x

1 = a xb

a

1 b

xa

Page 2 of 12 www.tuitionwithjason.sg

A-Math Formula List - Additional Math (4047) Surds a a÷ b= b

a × b = a×b

( a )=

m a ×n b = m× n a×b

2

a × a=

a

m a +n a = ( m + n) a

m a −n a = ( m − n) a

Rationalizing Denominator 1 n− a × = n+ a n− a

(n − n −(

1 n+ a × = n− a n+ a

(n + n −(

1 n+

1 n−

a

a

2

2

) a)

(n −

) a)

(n −

a

a

= 2

= 2

a

)

n −a 2

a

)

n −a 2

×

n− a = n− a

( n − a= ) (n − a ) n−a ( n) −( a)

×

n+ a = n+ a

( n + a= ) (n + a ) n−a ( n) −( a)

2

2

2

2

Partial Factions Linear Factor Check if the highest coefficient of the

mx + n A B = + (ax + b)(cx − d ) (ax + b) (cx + d )

NUMERATOR is the SAME or LARGER that the DENOMINATOR. If it is, do LONG DIVISION first before partial

Repeat Factor

fractions.

mx + n A B C = + + 2 (ax + b)(cx − d ) (ax + b) (cx + d ) (cx + d ) 2

Page 3 of 12 www.tuitionwithjason.sg

A-Math Formula List - Additional Math (4047) Quadratic Factor mx + n A Bx + C = + 2 (ax + b)(cx − d ) (ax + b) (cx 2 + d )

Logarithm log b 1 = 0

ln1 = 0

log b b = 1

ln e x = x

by = x can be covert to y = log b x

log b bx = x log b m + log b n = log b (m × n) log b m – log b n = log b (m ÷ n)

ln e xa = xa * log b (m × n) ≠ log b m × log b n

ln x = log e x ln e =1 as log e e=1

log b m a = a × log b m log v u =

log a u log a v

log = vu

log u u 1 = log u v log u v

Binomial Expansion n n! = r r !(n − r )!

n n = Cr r

n n n n n n bx)n a n (bx)0 + a n −1 (bx)1 + a n −2 (bx)2 + a n −3 (bx)3 .... a n −r (bx)r + a n −n (bx)n (a += 0 1 2 3 r n OR

n n n n a n + a n −1 (bx)1 + a n − 2 (bx) 2 + a n −3 (bx)3 .... a n − r (bx) r + (bx) n (a + bx) n = 1 2 3 r

Page 4 of 12 www.tuitionwithjason.sg

A-Math Formula List - Additional Math (4047) n (n)(n − 1) n − 2 (n)(n − 1)(n − 2) n −3 a n + a n −1 (bx)1 + a (bx) 2 + a (bx)3 .... + (bx) n (a + bx) n = 1 1× 2 1× 2 × 3

n n n n −1 n n−2 n n −( n −1) n 0 1 2 n −1 n ( kx ) + 1n−n ( kx ) 1 ( kx ) + 1 ( kx ) + 1 ( kx ) + .... 1 0 1 2 n − 1 n

kx ) (1 += n

OR

(1 + kx )

n

n n n n −1 n 1 2 = 1 + ( kx ) + ( kx ) + .... ( kx ) + ( kx ) 1 2 n − 1

Trigonometry

cos ecθ =

1 sin θ

sin 2 θ + cos 2 θ = 1

sec θ =

1 cos θ

1 + cot 2 θ = cos ec 2θ

cot θ =

1 cos θ = tan θ sin θ

1 + tan 2 θ = sec 2 θ

Compound Angle Formula

sin ( A= ± B ) sin A cos B ± cos A sin B

cos ( A ± B ) = cos A cos B sin A sin B

Page 5 of 12 www.tuitionwithjason.sg

A-Math Formula List - Additional Math (4047) tan A ± tan B tan ( A ± B ) = 1 tan A tan B

Double Angle Formula

sin 2 A = 2sin A cos A

cos = 2 A cos 2 A − sin 2 A

tan 2 A =

= cos 2 A 2 cos 2 A − 1

2 tan A 1 − tan 2 A

cos 2 A = 1 − 2sin 2 A

Half Angle Formula

sin

A 1 − cos A = ± 2 2

cos

A 1 + cos A = ± 2 2

A = tan 2

1 − cos A 1 − cos A = 1 + cos A sin A

R-Formula aCosθ ± bSinθ = RCos (θ α )

R Where=

aSinθ ± bCosθ = RSin(θ ± α )

tan α =

a 2 + b2

b a

Co-ordinate Geometry Gradient(m) =

y2 − y1 x2 − x1

Linear Graph Y= m x + c

y2 − y= m( x2 − x1 ) 1 m= gradient

General Equation

c= y-intercept (point on the graph that intersects the y-axis)

Y − y1= m( X − x1 ) where

( x1 , y1 ) is a point on the

graph.

Page 6 of 12 www.tuitionwithjason.sg

A-Math Formula List - Additional Math (4047) Mid-point of a line = (

x1 + x2 y1 + y2 , ) 2 2

Distance between two points =

( x2 − x1 ) 2 + ( y2 − y1 ) 2

If two lines have the same gradient

If two line have perpendicular

m1 = m2

gradient i.e. 90° to each other.

m1 = −

1 or m1 × m2 = −1 m2

Perpendicular Bisector

1. The two lines AB and PQ must intersect at 90°

m1 ( AB ) = −

1 m2 ( PQ)

2. One Line (AB) will cut the mid-point of the other line (PQ)

x2 + x1 y2 + y1 , 2 2

Mid-point PQ =

Area of Plane Figure (Polygon Figure)

Vertices A(x1,y1), B(x2,y2),C (x3,y3)

1 𝑥1 � 2 𝑦1

*It does NOT matter if you calculate in a

𝑥2 𝑥3 𝑦2 𝑦3

𝑥4 𝑦4

𝑥1 𝑦1 �

clockwise or anti-clockwise direction. The is a |modulus| in the formula

1 |(𝑥 𝑦 + 𝑥2 𝑦3 + 𝑥3 𝑦4 + 𝑥4 𝑦1 ) − (𝑥2 𝑦1 + 𝑥3 𝑦2 + 𝑥4 𝑦3 + 𝑥1 𝑦4 )| 2 1 2

Page 7 of 12 www.tuitionwithjason.sg

A-Math Formula List - Additional Math (4047) Circles Radius of a circle r=

( x − a ) 2 + ( y − b) 2

Equation of a Circle (𝑥 − 𝑎)2 + (𝑦 − 𝑏)2 = 𝑟 2 or

𝑥 2 + 𝑦 2 + 2𝑔𝑥 + 2𝑓𝑦 + 𝑐 = 0

where 𝑎 = −𝑔, 𝑏 = −𝑓 and 𝑟 = �𝑔2 + 𝑓 2 − 𝑐

Proofs in Plane Geometry Midpoint Theorem

Tangent –Chord Theorem (Alternate Segment Theorem)

sin If X and Y are midpoints, then

Angle W = Angle X

YZ // WX

Angle Y = Angle Z

YZ = ½ WX

Differentiation dy (ax n ) = anx n −1 dx

dy (ax) = a dx

dy (a) = 0 dx

Where’ a’ is a constant and ‘n’ is an integer.

Page 8 of 12 www.tuitionwithjason.sg

A-Math Formula List - Additional Math (4047) Chain Rule

Sum/Difference of Function

dy dy du = × dx du dx

d du dv (u ± v) = ± dx dx dx

Product Rule

Quotient Rule

d dv du (= uv) u + v dx dx dx

du dv v −u d u dx dx = dx v v2

d (sin x) = cos x dx

d (cos x) = − sin x dx

d (tan x) = sec 2 x dx

The functions below are obtained using chain rule.

d c ) ab cos(bx + c) a sin ( bx += dx

d −ab sin(bx + c) a cos ( bx + c ) = dx

d + c ) ab sec 2 (bx + c) a tan ( bx = dx

d a sin n ( bx = + c ) anb sin n −1 (bx + c) cos(bx + c) dx

d a cos n ( bx + c ) = − anb cos n −1 (bx + c) sin(bx + c) dx d ata n n ( bx = + c ) anb tan n −1 (bx + c) sec 2 (bx + c) dx

Exponential/Natural Logarithm Function d x (e ) = e x dx

d ax +b (e ) = ae ax +b (where a and b are constants) dx

d 1 (ln x) = (where x>0) dx x

d a [ln(ax + b)] = (where ax +b>0) dx ax + b

Page 9 of 12 www.tuitionwithjason.sg

A-Math Formula List - Additional Math (4047) Integration n dx ∫ ax=

ax n +1 + c where n≠1 n +1

∫ a dx= ax + c

∫ ( ax + b )

n

( ax + b )

= dx

n +1

(n + 1)(a )

+c

n≠1,a≠0; a & b are constants Product of constant and a function

Sum and Difference of function

∫ af ( x)dx = a ∫ f ( x)dx

∫ [α f ( x) ± β g ( x)]dx = α ∫ f ( x)dx ± β ∫ g ( x)dx

bx dx ∫ a cos=

where f(x) is a function

a sin bx + c b

a

− cos bx + c ∫ a sin bx dx = b

bx dx ∫ a sec= 2

a tan bx + c b

where x is in radian.

1 dx ln x + c where x>0 ∫x=

∫e

x

dx= e x + c

�

1 ln(𝑎𝑥 + 𝑏) 𝑑𝑥 = +𝐶 𝑎𝑥 + 𝑏 𝑎

�𝑒

𝑎𝑥+𝑏

𝑒 𝑎𝑥+𝑏 𝑑𝑥 = +𝐶 𝑎

�

1 ln(𝑎𝑥 2 + 𝑏𝑥) 𝑑𝑥 = +𝐶 𝑎𝑥 2 + 𝑏𝑥 2𝑎𝑥 + 𝑏

�𝑒

𝑎𝑥 2 +𝑏𝑥

2

𝑒 𝑎𝑥 +𝑏𝑥 𝑑𝑥 = +𝐶 2𝑎𝑥 + 𝑏

Page 10 of 12 www.tuitionwithjason.sg

A-Math Formula List - Additional Math (4047)

Integration of Area Area between Curve and X-axis 𝑏

∫𝑎 𝑓(𝑥)𝑑𝑥 Area between Curve and X-axis 𝑏

− ∫𝑎 𝑓(𝑥)𝑑𝑥 Area between Curve and Y-axis 𝑏

∫𝑎 𝑓(𝑦)𝑑𝑦 Area between Curve and Y-axis 𝑏

− ∫𝑎 𝑓(𝑦)𝑑𝑦

Area between the Curves f(x) (u-shape) and g(x)(n-shape). 𝑏

𝑏

� 𝑔(𝑥)𝑑𝑥 − � 𝑓(𝑥)𝑑𝑥 𝑎

𝑎

Area between the Curves g(x)(n-shape) and f(x)(u-shape). 𝑏

𝑏

−[� 𝑓(𝑥)𝑑𝑥 − � 𝑔(𝑥)𝑑𝑥] 𝑎

𝑎

Page 11 of 12 www.tuitionwithjason.sg

A-Math Formula List - Additional Math (4047) Area between the Curves g(y) (inverted c-shape) and f(y) (c-shape). 𝑏

𝑏

� 𝑔(𝑦)𝑑𝑦 − � 𝑓(𝑦)𝑑𝑦 𝑎

𝑎

Area between the Curves f(y) (c-shape) and g(y) (inverted c-shape). 𝑏

𝑏

−[∫𝑎 𝑓(𝑥)𝑑𝑥 − ∫𝑎 𝑔(𝑥)𝑑𝑥]

Kinematics Velocity is the RATE of CHANGE of

Acceleration is the RATE of CHANGE of

Displacement

Velocity

v=

ds dt

a=

where v: velocity,s:displacement, t:time = v

where a:accleration Some other methods to find acceleration

dv

a dt ∫ dt ∫= dt

= a

Displacement (s)

dv dt

𝑑𝑠 𝑑𝑡

Velocity (v)

� 𝑣 𝑑𝑡

d 2s dt 2

= a

𝑑𝑣 𝑑𝑡

dv ds × ds dt

Acceleration (a)

� 𝑎 𝑑𝑡 The End

Page 12 of 12 www.tuitionwithjason.sg

Thank you for interesting in our services. We are a non-profit group that run this website to share documents. We need your help to maintenance this website.

To keep our site running, we need your help to cover our server cost (about $400/m), a small donation will help us a lot.